EAP Courses in Joint-Venture Institutions: A Needs Analysis Based on Learner Perceptions - John Harper; Yachao Sun (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2022)
With the increase in English medium instruction (EMI) in non-English-speaking countries, the role of EAP in preparing learners for the academic tasks that they will face is enhanced. Joint-venture universities (JVUs), institutions formed in collaboration between foreign universities and universities in the host country, pose even greater challenges for EAP programs. Learners in JVUs are expected to meet the requirements of the collaborating institution while simultaneously developing skills in an additional language. Critical to the success of EAP programs in JVUs, then, is the careful analysis of learners’ needs and wants. The present study aims to provide insights into the needs and wants of EAP students at a China-based JVU by focusing on the perceptions of learners who have completed their EAP studies. Data were obtained through a narrative research method based on semi-structured interviews with 16 former EAP students and compared with stated program goals in an effort to discover areas in which students’ perceptions aligned or did not align with program goals. The paper presents cases of alignment and cases of mismatches. An analysis of the mismatches leads to the following pedagogical implications for EMI programs in JVUs: (1) Programs may better cater to learners’ interests by implementing a semi-negotiated curriculum; (2) programs may better cater to learners’ discipline-specific needs by providing broad writing topics for learners to refine in accordance with their particular disciplines; (3) programs may better promote the integration of EAP students and international students by consciously providing the initial “push” toward integration